F Faktor–Faktor yang Berhubungan Dengan Pengambilan Keputusan Penggunaan Kontrasepsi Intra Uterine Device (IUD) Pada WUS Di Puskesmas Rantau Pulut 1 - Yenny Okvitasari; Siti Rochani; Izma Daud (LPPM Universitas Sari Mulia, 2024)
Background: Contraception is a tool used to minimize the rate of population growth. Contraceptive methods are divided into 2 categories, namely MKJP and Non MKJP. Intra Uterine Device (IUD) is an ideal long-term contraceptive in an effort to prevent pregnancy. Objective: The purpose of this study was to determine the factors associated with decision making for the use of Intra Uterine Device (IUD) contraception in WUS. Methods: This study used a quantitative research design with a cross sectional approach. The sampling technique used total sampling and the number of respondents was 134 WUS family planning acceptors. Data collection using a knowledge questionnaire. Results: The results of the Chi Square statistical test showed a p value (0.001) < α = (0.05) on knowledge, p value (0.001) < α = (0.05) on age, p value (0.008) < α = (0.05) on education, p value (0.000) < α = (0.05) on knowledge indicating that Ho is rejected and Ha is accepted or there is a relationship between knowledge, age, education, husband's support for the low rate of decision making on the use of Intra Uterine Device (IUD). Conclusion: The results of the relationship between variables are strong where knowledge, age, education, husband's support is related to decision making on the use of contraceptive Intra Uterine Device (IUD) with so that more adequate counseling and education is needed about contraceptive Intra Uterine Device (IUD).